Analisa Intensitas Penggunaan Media Sosial dan Adiksi Internet Pada Mahasiswa Universitas Bina Darma - Mawardah, Mutia; Purnamasari, Susan Dian; Meinamara, Avia (Jurnal Ilmiah Psyche, 2023)
Abstract: The objective of this study is to establish the correlation between the level of social media usage and internet addiction among students at Bina Darma University, exploring the contributing factors and negative consequences of internet addiction on afflicted students. The hypothesis posits that there exists a connection between the intensity of social media usage and internet addiction among Bina Darma University students. The research employs a mixed-method approach, with a sample size comprising 226 students from Bina Darma University, and three students participating in interviews. Data collection utilizes purposive sampling, and the measurement tools include the social media usage intensity scale and the internet addiction scale. The analytical method applied in this research involves simple regression analysis. The findings reveal a highly significant relationship between the intensity of social media usage and internet addiction in Bina Darma University students, indicated by a correlation coefficient (r) of 0.205, a coefficient of determination (R²) of 0.042, and a p-value of 0.002 (p<0.001) in the simple regression test. Keywords: analysis, intensity, social media, internet addiction Abstrak: Penelitian ini bertujuan untuk mengidentifikasi korelasi antara tingkat intensitas penggunaan media sosial dan adiksi internet pada mahasiswa Universitas Bina Darma. Selain itu, penelitian ini juga mengeksplorasi faktor penyebab dan dampak negatif dari adiksi internet pada mahasiswa yang terkena dampaknya. Hipotesis penelitian menyatakan bahwa terdapat hubungan antara intensitas penggunaan media sosial dan adiksi internet pada mahasiswa Universitas Bina Darma. Metode penelitian yang diterapkan adalah metode kombinasi (Mixed Method). Sampel penelitian terdiri dari 226 mahasiswa Universitas Bina Darma, sementara tiga mahasiswa diwawancarai sebagai subjek penelitian. Pengumpulan data dilakukan melalui teknik purposive sampling, dengan menggunakan skala intensitas penggunaan media sosial dan skala adiksi internet sebagai alat ukur. Analisis data menggunakan teknik analisis regresi sederhana. Hasil analisis menunjukkan adanya hubungan yang signifikan antara intensitas penggunaan media sosial dan adiksi internet pada mahasiswa Universitas Bina Darma, dengan nilai koefisien korelasi (r) sebesar 0,205, koefisien determinasi (R²) sebesar 0,042, dan nilai p = 0,002 (p<0,001) pada uji regresi sederhana. Kata kunci: analisis, intensitas, media sosial, adiksi internet